Danish phase II trial using adipose tissue derived mesenchymal stromal cells for patients with ischaemic heart failure. (13th January 2023) - Qayyum, Abbas Ali; Mouridsen, Mette; Nilsson, Brian; Gustafsson, Ida; Schou, Morten; Nielsen, Olav Wendelboe; Hove, Jens Dahlgaard; Mathiasen, Anders Bruun; Jørgensen, Erik; Helqvist, Steffen; Joshi, Francis Richard; Johansen, Ellen Mønsted; et al.
Abstract: Aims: Patients suffering from chronic ischaemic heart failure with reduced left ventricular ejection fraction (HFrEF) have reduced quality‐of‐life, repetitive hospital admissions, and reduced life expectancy. Allogeneic cell therapy is currently investigated as a potential treatment option after initially encouraging results from clinical autologous and allogeneic trials in patients with HFrEF. We aimed to investigate the allogeneic Cardiology Stem Cell Centre Adipose tissue derived mesenchymal Stromal Cell product (CSCC_ASC) as an add‐on therapy in patients with chronic HFrEF. Methods and results: This is a Danish multi‐centre double‐blinded placebo‐controlled phase II study with direct intra‐myocardial injections of allogeneic CSCC_ASC. A total of 81 HFrEF patients were included and randomized 2:1 to CSCC_ASC or placebo injections. The inclusion criteria were reduced left ventricular ejection fraction (LVEF ≤ 45%), New York Heart Association (NYHA) class II‐III despite optimal anti‐congestive heart failure medication and no further revascularization options. Injections of 0.3 mL CSCC_ASC (total cell dose 100 × 10 6 ASCs) ( n  = 54) or isotonic saline ( n  = 27) were performed into the viable myocardium in the border zone of infarcted tissue using the NOGA Myostar® catheter (Biological Delivery System, Cordis, Johnson & Johnson, USA). The primary endpoint, left ventricular end systolic volume (LVESV), was evaluated at 6‐month follow‐up. The safety was measured during a 3‐years follow‐up period. Results: Mean age was 67.0 ± 9.0 years and 66.6 ± 8.1 years in the ASC and placebo groups, respectively. LVESV was unchanged from baseline to 6‐month follow‐up in the ASC (125.7 ± 68.8 mL and 126.3 ± 72.5 mL, P  = 0.827) and placebo (134.6 ± 45.8 mL and 135.3 ± 49.6 mL, P  = 0.855) group without any differences between the groups (0.0 mL (95% CI −9.1 to 9.0 mL, P  = 0.992). Neither were there significant changes in left ventricular end diastolic volume or LVEF within the two groups or between groups −5.7 mL (95% CI −16.7 to 5.3 mL, P  = 0.306) and −1.7% (95% CI −4.4. to 1.0, P  = 0.212), respectively). NYHA classification and 6‐min walk test did not alter significantly in the two groups ( P  > 0.05). The quality‐of‐life, total symptom, and overall summary score improved significantly only in the ASC group but not between groups. There were 24 serious adverse events (SAEs) in the ASC group and 11 SAEs in the placebo group without any significant differences between the two groups at 1‐year follow‐up. Kaplan–Meier plot using log‐rank test of combined cardiac events showed an overall mean time to event of 30 ± 2 months in the ASC group and 29 ± 2 months in the placebo group without any differences between the groups during the 3 years follow‐up period ( P  = 0.994). Conclusions: Intramyocardial CSCC_ASC injections in patients with chronic HFrEF were safe but did not improve myocardial function or structure, nor clinical symptoms.